Uptake of Molecular Species by Spherical Droplets and Particles Monitored Voltammetrically - Martinez-Ortiz, F; Laborda, E; Limon-Petersen, J; Rogers, E; Serna, C; Rees, N; Molina, A; Compton, R (2009)
The uptake of molecular species by spherical particles is diverse in nature ranging from amalgamation processes at mercury droplets through ion transfer through the spherical interface between two immiscible electrolyte solutions (ITIES) (droplets, vesicles, etc.) to monitoring events in and around individual biological cells. Such processes can be controlled and monitored using voltammetry. We report the full characterization of such systems with reverse and differential pulse voltammetry. In particular, the former is a very useful diagnostic tool because of the appearance of a unique peak-shaped response in the reverse pulse voltammetry curves that arises solely as a consequence of the depletion of the species inside the particle. The greater this effect is, the smaller the size of the particle. © 2009 American Chemical Society.